Projeto Observabaía: Patrimônio Cultural Subaquático da Baía de Todos os Santos. Relatório Parcial 2015 - Rodrigo de Oliveira Torres (Navigator)
The Baía de Todos os Santos (BTS), northeast Brazil, holds a rich underwater cultural heritage, with shipwreck sites ranging from 17th to 20th centuries, which have never been properly studied. This paper presents the partial results from Observabaía Project, which assessed 18 of these shipwreck sites, considering their Scientific Importance, Touristic Potential and Vulnerabilities. The data, collected from literature review, local dive shops informal interviews and inspection dives carried out between May and December 2015, were organized in a Geographic Information System. In conclusion, a scheme of Interpretative Underwater Trails is proposed, considering the management of underwater cultural resources of the BTS.